2017
DOI: 10.1021/acs.jpcb.7b07686
|View full text |Cite
|
Sign up to set email alerts
|

Probing Energy Landscapes of Cytochrome b6f with Spectral Hole Burning: Effects of Deuterated Solvent and Detergent

Abstract: In non-photochemical spectral hole burning (NPHB) and spectral hole recovery experiments, cytochrome bf protein exhibits behavior that is almost independent of the deuteration of the buffer/glycerol glassy matrix containing the protein, apart from some differences in heat dissipation. On the other hand, strong dependence of the hole burning properties on sample preparation procedures was observed and attributed to a large increase of the electron-phonon coupling and shortening of the excited-state lifetime occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(60 citation statements)
references
References 58 publications
2
57
0
Order By: Relevance
“…Concerning the most probable shape of the "blue" component, predominantly encoded into the holes, the results presented in Figure 1B suggest that it should be uniform / box-like. HGK and recovery results obtained for Cyt b6f in fully deuterated buffer-glycerol environment indicate that there are very little, if any, differences in the hole burning and recovery dynamics 17 . We conclude that spectral dynamics on the energy landscape tier characterized by the "blue" curve in Figure 3 definitely belongs to the protein, while the dynamics on the tier characterized by the black curve most likely belongs to the protein as well, but may with some small probability also be due to the movements of the -OH groups in the water/glycerol solvent surrounding the protein 17 .…”
Section: Distributionsmentioning
confidence: 88%
See 3 more Smart Citations
“…Concerning the most probable shape of the "blue" component, predominantly encoded into the holes, the results presented in Figure 1B suggest that it should be uniform / box-like. HGK and recovery results obtained for Cyt b6f in fully deuterated buffer-glycerol environment indicate that there are very little, if any, differences in the hole burning and recovery dynamics 17 . We conclude that spectral dynamics on the energy landscape tier characterized by the "blue" curve in Figure 3 definitely belongs to the protein, while the dynamics on the tier characterized by the black curve most likely belongs to the protein as well, but may with some small probability also be due to the movements of the -OH groups in the water/glycerol solvent surrounding the protein 17 .…”
Section: Distributionsmentioning
confidence: 88%
“…Attentive reader may notice that Eq. 3 contains extra factors of 2 in front of the ngr(gr) and the hopping probability, compared to similar equation from 10,11,17 . This modification reflects the fact that recovery of the spectral hole involves evolution of the system towards equilibrium, which must occur with the rate that is the sum of the "uphill" and "downhill" rates 19 .…”
Section: Figure 1 Presents An Example Of the Hole Growth Kinetics (Hgk) Data (Frame A Closelymentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of available low-temperature heat conductivity data for water, glycerol, other organic solvents, and some proteins suggested that bulk heat conductivity values required for observing the above effects are unrealistically low and the interface between the protein and the surrounding solvent is the only possible bottleneck for heat dissipation. 11 Alternatively, slowdown of the HGK with increased illumination intensity can be explained by introducing a three-state model, with one of these states being a long-lived triplet state. Here, we are going to demonstrate that the mismatch between the hole depths obtained with different techniques is also explainable invoking triplets.…”
Section: ■ Introductionmentioning
confidence: 99%